The Relationship of Knowledge and Attitudes with Behavior of Implementing Health Protocols in Garment Workers - Intan Mega Pratiwi; Indriati Paskarini; Endang Dwiyanti; Shintia Yunita Arini; Heru Suswojo (Universitas Airlangga, 2022)
Introduction: Informal workers in Garment Asia Raya of Banyuwangi continue their work activities during the COVID-19 pandemic. These informal workers in Garment Asia Raya Banyuwangi are, therefore, vulnerable to the transmission of COVID-19. The implementation of health protocols must be carried out to prevent and minimize the risk of COVID-19 transmission. However, the workers have not fully implemented health protocols. The purpose of this study is to determine the relationship of knowledge and attitudes with workers’ behavior in the implementation of health protocols. Methods: This study was a quantitative study with a cross-sectional research design. The research population was 50 informal workers in Garment Asia Raya Banyuwangi, using the total sampling technique. The variables studied were knowledge, attitudes and behavior in the implementation of health protocols. The data collection used a questionnaire sheet that had been tested for validity and reliability. The data analysis technique used was descriptive analysis and Spearman correlation analysis. Results: Most of the workers had a low category of knowledge. Most of the workers had a moderate attitude towards the implementation of health protocols. Moreover, most of the workers had poor behavior in implementing health protocols. The results showed a positive relationship with a weak correlation level between knowledge and attitudes with the behavior of implementing health protocols. Conclusion: It can be concluded that the higher the knowledge and attitudes of workers, the better the workers’ behavior in implementing health protocols.